The prognostic value of baseline 18F-FDG PET/CT in steroid-naïve large-vessel vasculitis: introduction of volume-based parameters - Dellavedova, L.; Carletto, M.; Faggioli, P.; Sciascera, A.; Del Sole, A.; Mazzone, A.; Maffioli, L. S. (European journal of nuclear medicine and molecular imaging, 2016)
Purpose The aim of this study was to analyse if the result of a baseline 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/CT scan, in large-vessel vasculitis (LVV) patients, is able to predict the course of the disease, not only in terms of presence/absence of final complications but also in terms of favourable/complicated progress (response to steroid therapy, time to steroid suspension, relapses, etc.). Methods A total of 46 consecutive patients, who underwent 18 F-FDG PET/CT between May 2010 and March 2013 for fever of unknown origin (FUO) or suspected vasculitis (before starting corticosteroid therapy), were enrolled. The diagnosis of LVV was confirmed in 17 patients. Considering follow-up results, positive LVV patients were divided into two groups, one characterized by favourable (nine) and the other by complicated progress (eight), on the basis of presence/absence of vascular complications, presence/absence of at least another positive PET/CT during follow-up and impossibility to comply with the tapering schedule of the steroid due to biochemical/symptomatic relapse. Vessel uptake in subjects of the two groups was compared in terms of intensity and extension. To evaluate the extent of active disease, we introduced two volume-based parameters: “volume of increased uptake” (VIU) and “total lesion glycolysis” (TLG). The threshold used to calculate VIU on vessel walls was obtained by the “vessel to liver” ratio by means of receiver-operating characteristic analysis and was set at 0.92 × liver maximum standardized uptake value in each patient. Results Measures of tracer uptake intensity were significantly higher in patients with complicated progress compared to those with a favourable one ( p < 0.05). Measures of disease extension were even more significant and TLG emerged as the best parameter to separate the two groups of patients ( p = 0.01). Conclusion This pilot study shows that, in LVV patients, the combined evaluation of the intensity and the extension of FDG vessel uptake at diagnosis can predict the clinical course of the disease, separating patients with favourable or complicated progress.